MORPHOMETRIC RELATIONSHIPS OF SPINELESS CUTTLEFISH, SEPIELLA INERMIS (ORBIGNY, 1848) FROM MUMBAI WATER - Sujit, Sundaram; Khan, Mohammad Zafar (Journal of Indian Fisheries Association, 2010)
The relationships of various morphometric characters with dorsal mantle length (DML) of Sepiella inermis from Mumbai waters was established. The coefficient of correlation (r2) for various morphometric characters against dorsal mantle length ranged from 0.747 to 0.942 indicating high degree of relationship among the characters compared. The regression of characteristics obtained by least squares method for S. inermis indicates that the characters have positive allometric growth. Â Key words: Morphometric relationships, Cuttlefish. Â